Uji Efisiensi dan Laju Fitoremidiasi Tanaman Apu-Apu Dengan Parameter Kadar COD (Chemical Oxygen Demand) Pada Air Tercemar Bensin - Witya Nur Yanti; Rena Jayana; Khoerun Nisa (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2021)
Apu-apu plants or commonly referred to as kiambang plants are a aquatic species that grow abundantly in wetlands. This abundance of aquatic plants can be used as a biofilter in addressing environmental problems particularly water pollution. This study is carried to test efficiency and fitoremidiation rate of apu-apu plants in lowering COD (Chemical Oxygen Demand) levels in gasoline contaminated water. A sample of apu-apu plant was taken from Karangkandri, Cilacap. After aclimatization, 15 apu-apu plant trees and 5 carp were placed in a container box that contained of contaminated water of 10 mL gasoline and then observed for pH, temperature and COD for six days. Temperature of contaminated water on 1st day is 28.5 oC and on 6th day is 27 oC. The value of the pH range of wastewater ranges is between 7.2-7.7. This suggests that wastewater is alkali mild. Phytoremediation ability of apu-apu plants in reducing COD levels has efficiency of 60%. This result indicates that the apu-apu plant is a good phytoremediator against contaminated water. The rate of phytoremediation or equal with COD decreasing at which apu-apu plants develop is 2.9 mg/L/day and goldfishes in contaminated water does not suffer death.